2009
DOI: 10.1371/journal.pone.0005884
|View full text |Cite
|
Sign up to set email alerts
|

The Malignant Pleural Effusion as a Model to Investigate Intratumoral Heterogeneity in Lung Cancer

Abstract: Malignant Pleural Effusions (MPE) may be useful as a model to study hierarchical progression of cancer and/or intratumoral heterogeneity. To strengthen the rationale for developing the MPE-model for these purposes, we set out to find evidence for the presence of cancer stem cells (CSC) in MPE and demonstrate an ability to sustain intratumoral heterogeneity in MPE-primary cultures. Our studies show that candidate lung CSC-expression signatures (PTEN, OCT4, hTERT, Bmi1, EZH2 and SUZ12) are evident in cell pellet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
63
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 57 publications
9
63
0
Order By: Relevance
“…A previous study revealed that CD44 high tumor cells are enriched for tumor propagating capacity, and that CD44 is a potential cancer stem cell (CSC) marker for NSCLC and other tumors (50,51). A recent study focusing on the metastatic ability of lung cancer cells obtained from malignant pleural effusion identified CD44 as a candidate marker for CSCs in malignant pleural effusion (52). Our study also found that CD44 is downregulated in response to restoration of LKB1 in lung cancer cells.…”
Section: Discussionsupporting
confidence: 68%
“…A previous study revealed that CD44 high tumor cells are enriched for tumor propagating capacity, and that CD44 is a potential cancer stem cell (CSC) marker for NSCLC and other tumors (50,51). A recent study focusing on the metastatic ability of lung cancer cells obtained from malignant pleural effusion identified CD44 as a candidate marker for CSCs in malignant pleural effusion (52). Our study also found that CD44 is downregulated in response to restoration of LKB1 in lung cancer cells.…”
Section: Discussionsupporting
confidence: 68%
“…Basak et al (45) studied the presence of CSC in malignant pleural effusions and reported CD44 as a possible stem cell marker but the characterization of stem cell-like properties was based on in vitro molecular analysis and cellular expansion only while Leung et al (43) reported both in vitro and in vivo tumorigenecity of CD44+ cells.…”
Section: Cd44mentioning
confidence: 99%
“…Jiang et al (54) were the first to isolate ALDH1-positive cells from human lung cancer cell lines and showed ALDH1-positive cancer cells exhibited the important CSC properties: in vitro selfrenewal, differentiation, and multidrug resistance capacities, expression of stem cell marker, in vivo tumor initiation, and occurrence of a heterogeneous population of cancer cells. Furthermore, they analyzed ALDH1 expression in 303 lung tissues from three different populations of patients with lung cancer, and reported that increased ALDH1 protein levels were positively associated with stage and grade of the tumors and inversely related to the patients' survival (45).…”
Section: Other Lung Csc Markersmentioning
confidence: 99%
“…Thus, nuclear β-catenin is a hallmark for active Wnt signaling [75]. As described above, Yagui-Beltrán, et al [87] and Peacock, et al [79] emphasized the potential importance of the Wnt signaling pathway in SCLC and NSCLC in addition to the Hedgehog signaling pathway. Also as described above, human primary or immortalized bronchial epithelial cells exposed to cigarette smoke became tumorigenic in nude mice, being associated with the activation of not only the Hedgehog signaling pathway but also the Wnt signaling pathway [80].…”
Section: Wnt Signaling Pathway and Nuclear β-Cateninmentioning
confidence: 99%
“…Among them, sphere-formation assays are utilized in a wide range of tissue systems including lung cancers [42,87]. However, each of these methods has potential pitfalls that complicate interpretation of the results.…”
Section: In Vitro Assaymentioning
confidence: 99%